When the Adoption Becomes Termination. Issue 4 (May 2015) - Cheung, Viola; Weitzman, Carol; Albers Prock, Lisa; Augustyn, Marilyn
Abstract : CASE: Steven is an 11-year-old boy who was adopted from an orphanage in Eastern Europe 8 years ago, when he was 3 years old along with his biological sister who is 1 year older. You have cared for him in your practice since that time seeing them annually for well child care. His mother reports that the first 2 years after adoption were very difficult, and Steven has never really bonded with her or her husband. Currently, he is reported to steal possessions of family members and instigate arguments with his older sister and act defiantly. The parents have put locks on their bedroom door due to fears of violence, primarily by Steven's older sister. Steven's mother reports that she and her husband no longer attempt to "parent" the children and provide minimal supervision to avoid conflict. In school, Steven is reported to have symptoms of inattention and hyperactivity that improved with treatment with stimulant medication and some learning challenges, but otherwise he is described as a lovely boy who has good relationships with his teachers. They present to urgent care clinic when mom stated "We have had enough." That day both children were caught taking $10 from the mother's wallet. On further discussion, it was discovered that they had done this several times over the last month to buy ice cream for neighborhood friends to "welcome them" to the neighborhood. Steven's mother presents today stating that the family has exhausted therapy services and are experiencing financial hardship secondary to investing time and money into behavioral and psychiatric services for Steven and his sister. They want to dissolve the adoption and have the children removed from their home. They seek guidance on how to do this. What would be your initial approach with the parents?